THE VOCABULARY LEARNING BEHAVIOR OF ROMANIAN HIGH SCHOOL STUDENTS IN A DIGITAL CONTEXT - COJCNEAN, Diana Maria (2017)
This thesis investigates the vocabulary learning behavior ofRomanian high school students in a digital context. The researchidentifies the vocabulary learning strategies used by EFL highschool students and focuses on how the choice of vocabulary learningstrategies varies across four independent variables: students’age, gender, academic profile (math‐ICT, humanities, science andeconomic‐technical) and language program (intensive English,bilingual, normal). These variables are hypothesized to influencelearners’ vocabulary behavior.